Present and future land suitability analysis for emerging fruit crops using spatial multicriteria decision systems - Quinta-Nova, L.C. (2021)
In recent years there has been an increase of investment in so called emerging fruit crops. It is agreed that the choice of uses and practices best suited to soil and climate conditions promotes the sustainable use of rural areas, with positive economic impacts. The objective of this study is to determine the suitability of emerging fruit crops based on the analysis of the limiting factors. The suitability was examined for the present time and in the face of two future emission scenarios (RCP 4.5 and 8.5). For this purpose, the biophysical criteria determining the cultivation of pistachio tree, strawberry tree and almond tree were processed using ArcGIS 10.8. The Analytical Hierarchy Process (AHP) was used to determine suitability for the crops. A pairwise comparison between environmental criteria (temperature, rainfall, chilling hours, crop heat units, relative humidity, topography, and soil proprieties) was performed to calculate the weights of these criteria. As a result of the AHP suitability maps for each crop in the present conditions, for the RCP 4.5 and the RCP 8.5 scenarios were produced. In the present conditions about 16.4% of the study area is classified as highly suitable for almond tree, 15.8% to strawberry tree, and 15.9% to pistachio tree. For the future scenarios, the area with high suitability will increase for almond tree and pistachio tree and will decrease for strawberry tree. It is the essential to be aware of the suitability and resilience of new crops to meet the need to adapt to climate change.